Effect of acetic acid concentration on functional group and microcrystalline structure of bituminous coal. (15th March 2021) - Yu, Yanbin; Yang, Haotian; Cheng, Weimin; Gao, Chengwei; Zheng, Lei; Xin, Qilin
Highlights: Acetic acid destroys the coal crystals and then recrystallizes to form crystals with a larger particle size. When the concentration of acetic acid is 15–16%, it has the greatest influence on the organic structure in coal. The concentration of acetic acid in 89–92% has the greatest influence on the crystal structure of coal. Abstract: The chemical dissolution of mineral components has a good effect on increasing the permeability of coal and oil reservoirs. At present, the accomplishments have focused on the analysis of the impact of strong corrosive acids on low porosity coal rocks. However, strong corrosive acids have safety problems, and their consumption rate is fast. The weak corrosive organic acid has little research on coalbed transformation, and the influence of weak acid on coal composition needs further study. In this study, Fourier transform infrared spectroscopy and X-ray diffraction are used to analyze coal samples that are treated with different concentrations of acetic acid. The results show that the functional groups in coal are sensitive to different concentrations of acetic acid, and acetic acid mainly acts to destroy the connection between molecules and hydroxyl groups, generating a large amount of OH. After soaking in 75% acetic acid, the reduction in coal is the highest, followed by 25%, followed by distilled water, and 50% acetic acid is the weakest. Acetic acid has a destructive effect on the crystals in coal. After the crystals are destroyed, the crystals are recrystallized to form crystals with a larger particle size, which loosens the whole and increases the porosity of the coal. Analysis and fitting of experimental data show that the concentration of acetic acid at 15% to 16% has the greatest effect on the organic structure of coal, and the concentration of acetic acid has the greatest effect on the crystal structure of coal within 89–92%.